2021
DOI: 10.1111/dgd.12734
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock cognate 70 genes contribute to Drosophila spermatocyte growth progression possibly through the insulin signaling pathway

Abstract: Drosophila spermatocytes grow up to 25 times their original volume before the onset of male meiosis. Several insulin‐like peptides and their cognate receptors (InR) are essential for the cell growth process in Drosophila. Here, we aimed to identify additional signaling pathways and other regulatory factors required for germline cell growth in Drosophila males. Spermatocyte‐specific expression of the dominant‐negative form of InR inhibits cell growth. Conversely, constitutively active forms of signaling factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Like VCP and sa , multiple of the de-repressed genes, including hsc70-2 and ubi-p63e , are required for meiotic progression (Azuma, et al, 2021; Lu, et al, 2013). We therefore hypothesized that genetically inhibiting H2Aub may rescue some aspects of germ-cell development in VCP -RNAi testes.…”
Section: Resultsmentioning
confidence: 99%
“…Like VCP and sa , multiple of the de-repressed genes, including hsc70-2 and ubi-p63e , are required for meiotic progression (Azuma, et al, 2021; Lu, et al, 2013). We therefore hypothesized that genetically inhibiting H2Aub may rescue some aspects of germ-cell development in VCP -RNAi testes.…”
Section: Resultsmentioning
confidence: 99%
“…As a highly conserved ER resident protein, GRP78 is involved in the folding and assembly of nascent proteins, serving as a master regulator of ER stress responses, facilitating cancer cell growth and viral replication [ 8 , 9 , 22 ]. GRP78 has been extensively studied in mammals [ 8 ], Drosophila [ 23 ], and fish [ 24 ]. However, the information regarding its molecular function in insect species is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The BmGRP78 exhibited a ubiquitous expression profile in different developmental stages and various tissues of B. mori , with the L4D3 stage and the gonad showing the highest transcription level. The evidence suggests that the GRP78 protein is an essential regulator of developmental processes in insects, and the mechanism of regulation may vary among different life stages and insect species [ 23 , 26 ]. GRP78 is reportedly associated with male reproduction, is expressed on the surface of human and rat sperm, and is associated with calcium-binding protein [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Hsc70-4 resulted in fly testes full of small undifferentiated germ cells [ 44 ]. Recent studies suggested that Hsc70-4 possibly targeted Akt or Pdk1 acting downstream of PI3K, thus regulating spermatocyte growth and meiosis initiation [ 57 ]. Therefore, the dramatic reduction of ubiquitinated Hsc70-4 by Wolbachia infection might damage germ cell differentiation in Drosophila testes.…”
Section: Discussionmentioning
confidence: 99%